Sexual maturity of Eurytium limosum (say 1818) from a subtropical mangrove in Brazil - Guimaraes, F. J.; Negreiros-Fransozo, M. L. (Kluwer Academic/plenum Publ, 2002)
The size at onset of maturity of Eurytium limosum from a subtropical mangrove in Brazil was investigated. In this species, sexual maturity for males can be indicated by the allometric growth and gonopod length. For females, the morphological sexual maturity can only be externally verified through the relative quantity of setae along the abdominal margins and pleopods. Internally, gonad development was also examined. The size at which half of the population is physiologically mature was 11.6 mm of CW for females and 12.3 mm of CW for males. The values for the morphological and physiological maturity are very similar, indicating that the development of the secondary sexual characters is synchronized with the achievement of the physiological maturity for E. limosum.